2019
DOI: 10.3390/nu11020213
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dairy and Plant-Derived Lactobacilli as Starters for Cherry Juice Fermentation

Abstract: Background: Lactic acid bacteria (LAB) exhibit a great biodiversity that can be exploited for different purposes, such as to enhance flavours or metabolize phenolic compounds. In the present study, the use of dairy and plant-derived LAB strains to perform cherry juice fermentation is reported. Methods: The growth ability of Lactobacillus plantarum, Lactobacillus casei, Lactobacillus paracasei and Lactobacillus rhamnosus was studied in cherry juice. Profiling of sugars, organic acids and volatile compounds was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 45 publications
3
60
2
1
Order By: Relevance
“…Therefore, orange peel allows the growth not only of L. plantarum , but also of the other LAB species assayed. Because all of the strains tested in the present study were isolated from dairy products, it can be confirmed that LAB strains isolated from different niches are able to be adapted to plant matrices …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, orange peel allows the growth not only of L. plantarum , but also of the other LAB species assayed. Because all of the strains tested in the present study were isolated from dairy products, it can be confirmed that LAB strains isolated from different niches are able to be adapted to plant matrices …”
Section: Resultsmentioning
confidence: 99%
“…Because all of the strains tested in the present study were isolated from dairy products, it can be confirmed that LAB strains isolated from different niches are able to be adapted to plant matrices. 39 As can be seen in Fig. 3(A), not all strains consumed the same quantity of RS and the consumption speed was different depending on the LAB species.…”
Section: Evaluation Of La Production By Different Lab Strains On Oranmentioning
confidence: 89%
“…Furthermore, some phenolic compounds, showing antimicrobial activity, can be increased or produced ex novo during lactic acid fermentation [27]. Some studies reported the production of phenyllactic acids from LAB and the antimicrobial activity of these compounds has been widely documented on pathogenic microorganisms [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…also validated that the utilization of dairy‐ and plant‐derived LAB in the fermentation of cherry juice resulted in the metabolic transformation of several phenolic compounds in the substrate. Specifically, hydroxycinnamic acids such as caffeic and p ‐coumaric acids were metabolized by LAB into dihydrocaffeic acid and p ‐vinylphenol, respectively, by phenolic acid decarboxylases or phenolic acid reductases . Moreover, Valero‐Cases et al .…”
Section: Discussionmentioning
confidence: 99%